VERNACULAR ARCHITECTURE AND CLIMATE RESPONSIVENESS: SUSTAINABLE DESIGN STRATEGIES IN CENTRAL ASIA - Hamidova Mohigul Hayotovna; Vohidov Shakhzod Kenjayevich (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article explores the significance of vernacular architecture in achieving climate-responsive and sustainable building design in Central Asia, with a focus on Uzbekistan. Traditional architectural practices in the region, developed over centuries, demonstrate remarkable adaptability to harsh climatic conditions such as extreme heat, low humidity, and limited water resources. The study analyzes key design elements like thick mudbrick walls, courtyard planning, and wind catchers (badgirs), and evaluates their relevance in modern construction. The findings highlight the need to integrate indigenous architectural wisdom with contemporary technology to promote energy efficiency, environmental harmony, and cultural continuity.